IgA nephropathy in a young adult with nephrotic syndrome: Case report - Cassis,João (2017)
IgA nephropathy has many clinical presentations, of which nephrotic syndrome is possibly the rarest. Recently, the association of IgA nephropathy with minimal change disease was better described with patients having complete response to steroid therapy and no progression to CKD. We report a similar case in a young male presenting with nephrotic syndrome